2012
DOI: 10.1186/1471-230x-12-58
|View full text |Cite
|
Sign up to set email alerts
|

Unsedated peroral wireless pH capsule placement vs. standard pH testing: A randomized study and cost analysis

Abstract: BackgroundWireless capsule pH-metry (WC) is better tolerated than standard nasal pH catheter (SC), but endoscopic placement is expensive. Aims: to confirm that non-endoscopic peroral manometric placement of WC is as effective and better tolerated than SC and to perform a cost analysis of the available esophageal pH-metry methods.MethodsRandomized trial at 2 centers. Patients referred for esophageal pH testing were randomly assigned to WC with unsedated peroral placement or SC after esophageal manometry (ESM). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The present and Andrews et al 2 studies observed that there was no significant difference between the capsule or catheter introduction. However, Gillies et al 11 showed less discomfort in the introduction of the capsule (p<0.0001).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…The present and Andrews et al 2 studies observed that there was no significant difference between the capsule or catheter introduction. However, Gillies et al 11 showed less discomfort in the introduction of the capsule (p<0.0001).…”
Section: Discussionsupporting
confidence: 45%
“…By comparing discomfort and interference in routine activities between wireless and conventional pH test, during the monitoring, Andrews et al, Gillies et al, and Wong et al 2,11,34 observed better tolerability of the capsule. There was significantly less discomfort (nasal pain, runny nose, cervical pain, cervical discomfort and headache), as well as less interference in daily activities (general activities, eating, work and sleep) 2,11,34 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of articles (n=15) used a public healthcare system perspective ( e.g . UK NHS, US Medicare) [917,1923,26]. One study used an employer cost perspective [18], one used a societal perspective [24], and one used a third party payer perspective [25].…”
Section: Resultsmentioning
confidence: 99%
“…In this questionnaire (which is presented in its original French version and a translated English version in the Appendix S1), patients rate their overall experience (overall discomfort, overall pain, overall psychological distress, whether they would do the test again, and global satisfaction), as well as the occurrence of various adverse effects (pain, discomfort, nausea, vomiting, coughing, choking, or others), and their severity (on a scale of 1 to 10) during three test phases: (a) catheter insertion, (b) test recording, and (c) in patients undergoing apH only, at home recording. This questionnaire was developed before the study and is based on Andrews et al's patient questionnaire and the American Society for Gastrointestinal Endoscopy (ASGE) patient satisfaction survey for endoscopy…”
Section: Methodsmentioning
confidence: 99%